Role of angiotensin II in the development of subcellular remodeling in heart failure - Sukhwinder K. Bhullar; Anureet K. Shah; Naranjan S. Dhalla (Open Exploration Publishing Inc., 2021)
The development of heart failure under various pathological conditions such as myocardial infarction (MI), hypertension and diabetes are accompanied by adverse cardiac remodeling and cardiac dysfunction. Since heart function is mainly determined by coordinated activities of different subcellular organelles including sarcolemma, sarcoplasmic reticulum, mitochondria and myofibrils for regulating the intracellular concentration of Ca2+, it has been suggested that the occurrence of heart failure is a consequence of subcellular remodeling, metabolic alterations and Ca2+-handling abnormalities in cardiomyocytes. Because of the elevated plasma levels of angiotensin II (ANG II) due to activation of the renin-angiotensin system (RAS) in heart failure, we have evaluated the effectiveness of treatments with angiotensin converting enzyme (ACE) inhibitors and ANG II type 1 receptor (AT1R) antagonists in different experimental models of heart failure. Attenuation of marked alterations in subcellular activities, protein content and gene expression were associated with improvement in cardiac function in MI-induced heart failure by treatment with enalapril (an ACE inhibitor) or losartan (an AT1R antagonist). Similar beneficial effects of ANG II blockade on subcellular remodeling and cardiac performance were also observed in failing hearts due to pressure overload, volume overload or chronic diabetes. Treatments with enalapril and losartan were seen to reduce the degree of RAS activation as well as the level of oxidative stress in failing hearts. These observations provide evidence which further substantiate to support the view that activation of RAS and high level of plasma ANG II play a critical role in inducing subcellular defects and cardiac dysfunction during the progression of heart failure.